A morphology-based phylogeny of the Liolaemus alticolor–bibronii group (Iguania: Liolaemidae) - Quinteros, Andrés Sebastián (Zootaxa, 2013)
The genus Liolaemus was split in two subgenera, Liolaemus sensu stricto and Eulaemus. Inside the Liolaemus sensu stricto subgenus, many groups have been proposed. One of them is the L. alticolor-bibronii group. Here, I studied 184 morpho-logical characters of more than one thousand specimens that of the L. alticolor-bibronii group. Many of these characters are original from this study, especially the characters related to color pattern. Also, I include eight population without tax-onomic status. Using those characters and terminal taxa, I performed phylogenetic analyses using parsimony as optimality criterion, under implied weight. Two difpferent topologies were found. The results show that the L. alticolor-bibronii group is monophyletic, and that it is sister to the L. gravenhorsti group. This finding is congruent with previous morpho-logical and molecular phylogenies. Also, nested within the L. alticolor-bibronii group the L. lemniscatus and the L. robert-mentensi groups are found. In contrast to previous hypotheses, Liolaemus tacnae is never recovered as a member of the L. alticolor-bibronii group.